1997
DOI: 10.1079/bjn19970188
|View full text |Cite
|
Sign up to set email alerts
|

Free-living energy expenditure of adult men assessed by continuous heart-rate monitoring and doubly-labelled water

Abstract: Free-living energy expenditure was estimated by doubly-labelled water (DLW) and continuous heart-rate (HR) monitoring over nine consecutive days in nine healthy men with sedentary occupations but different levels of leisure-time physical activity. Individual calibrations of the HRenergy expenditure (EE) relationship were obtained for each subject using 30 min average values of HR and EE obtained during 24 h whole-body calorimetry with a defined exercise protocol, and additional data points for individual leisu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 24 publications
1
42
0
2
Order By: Relevance
“…HR was recorded on an average of 1 min intervals from the ®rst waking hour until removal close to (Davidson et al, 1997).…”
Section: Subject Calibrationmentioning
confidence: 99%
“…HR was recorded on an average of 1 min intervals from the ®rst waking hour until removal close to (Davidson et al, 1997).…”
Section: Subject Calibrationmentioning
confidence: 99%
“…Although there is no reason to believe that there would be any significant bias in the DLW-derived group mean energy expenditure (Haggarty et al, 1994a, b), the technique is not perfect. Some of the within-individual disagreement when comparing the two methodologies can be ascribed to the expected variability in DLW derived energy expenditure (Davidson et al, 1997).…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…In contrast, the women who were also lean (BMI 20·2 kg/m 2 ), walked half the distance of the men (5·8 km/d), with lower PAL (1·78; range 1·44-2·53). Also studies of lean UK subjects with high levels of leisure physical activity have been shown to have PAL values that are consistent with their activity (74) . For this group of healthy lean men (BMI 21·6 (SD 1·5) kg/m 2 , age 38 (SD 9) years), with sedentary jobs but most of whom (seven out of nine) reported active leisure activities, the active men exhibited high PAL (mean 2·12; range 1·79-2·41) and for competitive runners in training, mean PAL was 2·2 (range 2·02-2·41).…”
Section: How Is Physical Activity Level Related To Actual Behaviouralmentioning
confidence: 99%
“…2 (51) , of the studies showing study mean PAL values $2·0 (n 15; six women and nine men), three were from low or moderate developed societies, seven were overweight or obese, all were aged less than 65 years and most studies were very small (median n 8). However, as indicated above, PAL values in excess of 2·0 were recorded in DLW studies of lean adult subjects in which either sedentary jobs were accompanied by high leisure activities (74) , or who exhibited high activity lifestyles (African (71) or South American farmers (72) ) or African hunter -gatherer men (73) for whom walking long distances was recorded. Thus a population PAL for the UK in 1955 considerably higher than currently assumed values is certainly possible.…”
Section: Changes In Food Intake In the Ukmentioning
confidence: 99%